Reo- and thixocompacting - new approaches to casting of materials in hard-fluid state - N. K. Tolochko; Ju. A. Shienok; A. Z., Mjaldun; S. E. Mozzharov (Литьë и металлургия)
There are offered and examined the two new methods of casting in solid-liquid state—reo- and thixocompacting- useful for casting with the fixed fusion point. There are determined the conditions of these methods realization and experimentally analyzed on the model substances the processes and structure peculiarities of the produced casts.